2015
DOI: 10.1159/000381768
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Investigation of Graves' Disease and Selenium: Thyroid Hormones, Auto-Antibodies and Self-Rated Symptoms

Abstract: Background: In Graves' thyrotoxicosis tachycardia, weight loss and mental symptoms are common. Recovery takes time and varies between patients. Treatment with methimazole reduces thyroid hormone levels. According to previous research, this reduction has been faster if selenium (Se) is added. Objective: The objective was to investigate whether supplementing the pharmacologic treatment with Se could change the immune mechanisms, hormone levels and/or depression and anxiety. Methods: We prospectively investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 30 publications
3
37
0
7
Order By: Relevance
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%
“…У численних дослідженнях доведено ефектив-ність застосування селеновмісних засобів у пацієн-тів із цим захворюванням [1,5,12,16,31,32].…”
Section: том 13 № 1 2017unclassified
“…При цьому погіршен-ня перебігу захворювання встановлено тільки в 7 % пацієнтів, які отримували селен, проти 26 % осіб, які приймали плацебо [21]. Аналогічні результати були отримані при проведенні інших досліджень [5,27].…”
Section: том 13 № 1 2017unclassified
“…В 2015 г. в Стокгольме было проведено исследо-вание, целью которого являлась оценка влияния фармакотерапии Se на иммунные механизмы, уро-вень тиреоидных гормонов, депрессии и тревоги у пациентов с БГ [14]. В исследование были включе-ны 38 пациентов с впервые выявленной БГ, которые ранее не получали терапию.…”
unclassified
“…Противоречивые результаты получены в недавно проведенных исследованиях Se в комплексной тера-пии БГ J. Calissendorff [14] (Швеция) и M. Leo [15] (Италия). В шведском исследовании (9 мес терапии) было отмечено статистически достоверное улучше-ние показателей биохимического контроля тирео-токсикоза у пациентов с впервые выявленной БГ на фоне тиреостатической терапии + Se, в итальянском исследовании (3 мес терапии) статистически значи-мых отличий по показателям биохимического кон-троля тиреотоксикоза между группами метимазола + Se и метимазола не наблюдалось.…”
unclassified